2020
DOI: 10.1002/ptr.6930
|View full text |Cite
|
Sign up to set email alerts
|

A pentamethoxylated flavone from Glycosmis ovoidea promotes apoptosis through the intrinsic pathway and inhibits migration of MCF‐7 breast cancer cells

Abstract: The rare flavone 5,3′‐dihydroxy‐3,6,7,8,4′‐pentamethoxyflavone (PMF) has been isolated from several plant species, and its cytotoxic activity has been reported against many types of cancer cells. In this study, PMF was purified from Glycomis ovoidea collected in Vietnam, and its antiproliferative effects and underlying mechanism of action were investigated against MCF‐7 cells. PMF inhibited growth in MCF‐7 > MCF‐10A > MDA‐MB‐231 cells after 72 hr treatment, with IC50 values of 1.5, 1.9, and 8.6 μg/ml, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A natural flavone compound, 5,3′-dihydroxy-3,6,7,8,4′-pentamethoxyflavone (PMF), was reported to induce an intrinsic apoptotic pathway in MCF-7 cells via enhancing the expression of Bax, Cyt-C, and PARP-1, decreasing the Bcl-2 level. 96 Some other natural products, like Tracheloside (TCS) and Deoxypodophyllotoxin (DPT), could significantly inhibit the growth of CRC cells. 97 , 98 …”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…A natural flavone compound, 5,3′-dihydroxy-3,6,7,8,4′-pentamethoxyflavone (PMF), was reported to induce an intrinsic apoptotic pathway in MCF-7 cells via enhancing the expression of Bax, Cyt-C, and PARP-1, decreasing the Bcl-2 level. 96 Some other natural products, like Tracheloside (TCS) and Deoxypodophyllotoxin (DPT), could significantly inhibit the growth of CRC cells. 97 , 98 …”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…Sideritoflavone inhibited JIMT 1 cell line migration but enhanced their motility by causing an increase in p65/NF-κΒ and activation of TGF-β signaling pathway (Sotillo et al, 2021). These findings can be compared to those of Anaya-Eugenio et al who also concluded that PMF inhibited migration of MCF-7 cells through reduced expression of p65/NF-κΒ (Anaya-Eugenio et al, 2021). Yao et al established that wogonoside exhibited antimetastatic effect through an array of mechanisms which included suppression of EMT in addition to inhibition of invasion and migration of TNF-α induced MDA-MB-231, MDA-MB-435, and BT-474 cells and TNF-α + TGF-β1-induced MCF7 cells (Yao et al, 2017).…”
Section: Inhibition Of Migration and Invasion (Anti-metastasis)mentioning
confidence: 70%
“…Cell viability using the MTT assay seemed to form a baseline against which a metabolite qualifies for further investigation. The studied flavonoids mainly displayed a dose and time-dependent effect on the variant breast cancer cell lines tested (Anaya-Eugenio et al, 2021;Attari et al, 2021;Go et al, 2018;Hallman et al, 2017;Hart et al, 2018;Hwang et al, 2020;Jia et al, 2018;Karimi et al, 2017;Li et al, 2017Li et al, , 2018Liang et al, 2021;Moradi et al, 2020;Qiu et al, 2019;Wang et al, 2021;Yu et al, 2018). The sensitivity of the flavonoids differed based on flavonoid type, concentration and cell line used.…”
Section: Cell Viabilitymentioning
confidence: 99%
See 2 more Smart Citations